(untitled) (Fiep Bulletin - online, 2014)
Building on statements and research findings from the last ten years there is little improvement to report in the field of inclusive physical education (IPE). The legislations of the European countries had changed towards inclusive education in the end of the 1990ies but teacher education and practical realization still seem to stay behind the theoretical intentions. Consulting recent international literature reviews (Block & Obrusnikova, 2007; O’Brien, Kudlacek & Howe, 2009); Kudlacek, Morgulec-Adamowicz & Verellen, 2010) similar problems are confirmed and only few good quality studies are conducted in Europe. Recalling the conclusions of my presentation at the FIE P congress in 2007 • Gap between theory and practice • Stagnation of inclusive developments in PE • PE teachers don’t get sufficient and qualitative education • PE teachers discover their teaching styles through “learning by doing” this contribution will ask questions and will try to suggest provisions for the improvement of the problematic areas which are often reported to be the challenges of IPE by teachers and researchers. The questions are: • How to deal with the growing complexity and heterogeneity with respect to gender, ability, ethnicity or religion in regular and inclusive PE? • How to improve the situation of lack of facilities and appropriate equipment? • How to enhance teachers’ competences and their need for personal and financial support?